Optimizing Brand Loyalty: The Effectiveness of Influencer Marketing and Digital Content Campaigns Mediated By Consumer Trust - Aldi, Muhammad; Adisaputra, Whisnu (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2024)
This study explores how influencer marketing and digital content campaigns affect brand loyalty, with consumer trust acting as a mediator, within Polewali Mandar Regency. Using a quantitative approach and Structural Equation Modeling (SEM), data were gathered from 100 local consumers who interacted with these marketing tactics. The findings indicate that influencer marketing and digital content campaigns significantly boost consumer trust, which in turn, greatly impacts brand loyalty. The model accounts for 52% of the variance in consumer trust and 62% in brand loyalty, underscoring the success of these digital strategies. Direct effects show strong connections between influencer marketing, digital content campaigns, consumer trust, and brand loyalty, while indirect effects highlight the essential role of consumer trust as a mediator. These results support existing research that emphasizes the importance of trust in building lasting consumer relationships. The study suggests that businesses should focus on trust-building in their digital marketing strategies to enhance brand loyalty. By creating engaging and credible content, businesses can foster consumer trust, leading to higher customer retention and long-term business success. This research offers valuable insights for local businesses in Polewali Mandar Regency to optimize their digital marketing efforts, ensuring lasting customer engagement and loyalty.